Critical review about MDM2 in cancer: Possible role in malignant mesothelioma and implications for treatment. (January 2016) - Urso, Loredana; Calabrese, Fiorella; Favaretto, Adolfo; Conte, PierFranco; Pasello, Giulia
Highlights: p53 is an oncosuppressor protein regulated by MDM2. p53 might be wild-type in malignant pleural mesothelioma. MDM2 has p53-independent functions, such as neoangiogenesis induction. MDM2 might be a promising target for anticancer treatment. MDM2-p53 inhibitors have not been clinically investigated in mesothelioma so far. Abstract: The tumor suppressor p53 regulates genes involved in DNA repair, metabolism, cell cycle arrest, apoptosis and senescence. p53 is mutated in about 50% of the human cancers, while in tumors with wild-type p53 gene, the protein function may be lost because of overexpression of Murine Double Minute 2 (MDM2). MDM2 targets p53 for ubiquitylation and proteasomal degradation. p53 reactivation through MDM2 inhibitors seems to be a promising strategy to sensitize p53 wild-type cancer cells to apoptosis. Moreover, additional p53-independent molecular functions of MDM2, such as neoangiogenesis promotion, have been suggested. Thus, MDM2 might be a target for anticancer treatment because of its antiapoptotic and proangiogenetic role. Malignant pleural mesothelioma (MPM) is an aggressive asbestos-related tumor where wild-type p53 might be present. The present review gives a complete landscape about the role of MDM2 in cancer pathogenesis, prognosis and treatment, with particular focus on Malignant Pleural Mesothelioma.